PENGARUH KREDIT PERBANKAN TERHADAP PERTUMBUHAN EKONOMI DIK PROVINSI KALIMANTAN BARAT - B61112047, TAUFIK (Jurnal Ekonomi Daerah (JEDA), 2014)
ABSTRACT The research is a descriptive study intended to get an answer that how much realization influence of the banking loans that is investments loans, working capital loans, consumer loans on the level of economic growth in the province of West Kalimantan either partially or simultaneously and independent of all the variables are studied, which is the most dominant variable in affecting the rate of economic growth and after researched using SPSS (Statistical Package for Software social Sciense) ver. 17.0, it can be concluded that : In Partial variables of investment loans, working capital loans and investments significantly affect toward economic growth in the province of West Kalimantan and for working capital loans has the most dominant influence with coefficient of 16.8 % , investment loans coeffecient of 9.8 % and consumption loans coffecient of 9.1 %. Together (simultaneously) these variables also affect the economic growth , with a significant 0.000< α = 0.05 ( visible ) in Table 4.8. besides that ​​in Table 4.7 known adjustment values r square of 975, or 97.5 %, this proves that economic growth of West Kalimantan Province was heavily influenced by those credit variables. Banks in West Kalimantan and the relevant government in the future to do synergize strategic to push and deceptive loans in the UMKM sector (Micro, Small and Medium Enterprises) productively , especially in the province of West Kalimantan. . Keywords : Banking Loans and Economic Growth